HPV Vaccine utilization, Alberta 2008/09 – 2013/14 School year. Issue 1 (December 2015) - Liu, Xianfang; Bell, Christopher; Simmonds, Kimberley; Russell, Margaret; Svenson, Lawrence
Abstract Background In Canada both bivalent (bHPV) vaccine and quadrivalent HPV vaccine (qHPV) are authorized for use. In Alberta, while both vaccines are available for private purchase, only qHPV is publicly funded for school girls in grades 5 and 9 as of 2013. We describe HPV vaccine uptake in Alberta, by school year, from the start of the publicly funded program in the Fall of 2008 through to August 31st 2014 and estimate the cumulative proportion of the female population who were vaccinated by the end of the 2013/14 school year. Methods We used data from the Alberta Ministry of Health Immunization and Adverse Reaction to Immunization repository (publicly funded vaccine), the population-based Pharmaceutical Information Network information systems (privately purchased vaccine) for the period September 1, 2008 to August 31, 2014 and demographic data from the Alberta Health Care Insurance Plan Registry. We estimate vaccine uptake rates and explore them by attributes of person, time, place, vaccine funding, and number of doses received. We estimated the cumulative proportions of the female population (by age group and number of doses received) who had received HPV vaccine by the end of the 2013/14 school year. Results Of the 169, 259 unique individuals who received one or more doses of HPV vaccine over the period, 98.3 % were females, and 83.8 % received publicly funded vaccines. Vaccine uptake increased over the period. The cumulative proportion of females aged 9–26 years as of 2013/14 who had received two or more doses of vaccine was 34.3 %; for those aged 10–11 years 59.6 % and for those aged 14–15 years, 76.0 %. For those aged 9–26 years, 31.3 % had received three doses of vaccine. Conclusion HPV vaccine uptake rates have increased in Alberta over the study period, most prominently among the age groups targeted by the publicly funded school-girl vaccine program.